PENERAPAN SCAFFOLDING UNTUK MENINGKATKAN KETERAMPILAN DAN KREATIVITAS PESERTA DIDIK PADA PEMBELAJARAN SENI BUDAYA KELAS VII B SMPN 4 MALANG - Febria Saputri (Universitas Negeri Malang, 2024)
Abstract: This research aims to describe the application of the scaffolding method to improvestudents' skills in arts and culture learning for class VII B SMPN 4 Malang. Apart fromthat, it also analyzes the relationship between the application of scaffolding and thestudents' advanced abilities and need for guidance. This research uses a qualitativeapproach. The methods used to compile this article are literacy studies and fieldobservations. Literacy studies are carried out by analyzing detailed informationfrom several literacy and documentation sources. Field observations were carriedout by observing in depth the application of scaffolding in arts and culture learningat SMPN 4 Malang over a certain period of time. The application of scaffolding iscarried out optimally by providing assistance and guidance in demonstratingtechniques and processes in developing combinations and gradations in design toless advanced students. Apart from that, for advanced students, teachers becomefacilitators for advanced students by providing opportunities to become mentorsfor less advanced students. This scaffolding method provides maximumachievement in improving students' skills and abilities and providing meaningfulexperiences